POSSIBILITY OF RURAL SECTOR DEVELOPMENT IN SERBIA USING IPARD PROGRAM - Glušcević, Slađana; Maksimović, Sanja; Pejanović, Radovan; Simeunović, Teodor (Economics of Agriculture, 2017)
For the countries of the Western Balkans, especially in Serbia, whose economy is largely dependent on agriculture, strategically, within the accession negotiations with the European Union, topics concerning the rural sector are of great importance. In this sense, it is very important for all countries in the region, including Serbia to create the conditions for the implementation of IPARD - Instrument for Pre-Accession Assistance for Rural Development as the EU pre-accession program. This European instrument which helps countries that are at the door of the EU is actually a preparation for future participation in the complex and clearly defned Common agricultural policy of the European Union (CAP – Common agriculture policy), which is a set of rules equal for all and that means common agricultural budget. The importance of being well-prepared for the CAP, is expressed in the fact that this budget is more than half of EU cash. When a country joins the EU, it is given a quota in the common agricultural budget through two funds - EAFRD (European Agricultural Fund for Rural Development) and EAGF (European Agricultural Guarantee Fund), and for a national agriculture to effectively adopt the mode of operation of these instruments, it is important that the funds which are at its disposal in the pre-accession period are better utilized, and to master the principles on which CAP is based. First steps in the use of further more generous funds for agriculture and rural development are laid down through IPARD.